Perception and Willingness to Use Telepharmacy Among the General Population in Jordan - Abu-Farha, Rana; Alzoubi, Karem H.; Abu Assab, Mohammad; Awwad, Oriana; Gharaibeh, Lobna; Mukattash, Tareq L.; Halboup, Abdulsalam M. (Dove Medical Press, 2023)
Objective: This research aimed to explore how telepharmacy is perceived, whether it would be willingly used by the overall population in Jordan, and the associated socioeconomic disparities that might affect its acceptance. Methods: This is a survey-based cross-sectional study involving the general public of Jordan. The study took place in various Jordanian cities from May 2nd to June 1st, 2023. Using Google forms, the questionnaire was shared through various social media channels (such as Facebook and WhatsApp). Results: The questionnaire received responses from 800 participants. The data showed that a sizable portion of the Jordanian population were unaware of telepharmacy (n= 343, 42.9%), and a majority had never utilized it (n= 131, 16.4%). The participants viewed the main advantage of telepharmacy as minimizing unnecessary trips to pharmacies (n= 668, 83.5%) and reducing travel time and expenses (n= 632, 79.0%). However, the primary concern was the mental effort required to use this service (n= 465, 58.1%). Of the respondents, 61.3% (n= 490) indicated a willingness to adopt telepharmacy services in the future. Regression analysis indicated that men were more likely to use this service compared to women (OR= 1.947, p< 0.001), and people living in northern and southern Jordan exhibited a greater willingness compared to those inhabiting the central region (OR= 2.168, p< 0.001). Conclusion: The results reveal a positive attitude towards and a significant readiness to embrace telepharmacy among the Jordanian population. However, for broader acceptance and utilization, apprehensions regarding the service need to be addressed. Doing so could improve access to pharmaceutical care, particularly for patients living in far-flung areas of Jordan.